Actinobacillus pleuropneumoniae biofilms: Role in pathogenicity and potential impact for vaccination development. (7th November 2017) - Hathroubi, Skander; Loera-Muro, Abraham; Guerrero-Barrera, Alma L.; Tremblay, Yannick D. N.; Jacques, Mario
Abstract: Actinobacillus pleuropneumoniae is a Gram-negative bacterium that belongs to the family Pasteurellaceae . It is the causative agent of porcine pleuropneumonia, a highly contagious respiratory disease that is responsible for major economic losses in the global pork industry. The disease may present itself as a chronic or an acute infection characterized by severe pathology, including hemorrhage, fibrinous and necrotic lung lesions, and, in the worst cases, rapid death. A. pleuropneumoniae is transmitted via aerosol route, direct contact with infected pigs, and by the farm environment. Many virulence factors associated with this bacterium are well characterized. However, much less is known about the role of biofilm, a sessile mode of growth that may have a critical impact on A. pleuropneumoniae pathogenicity. Here we review the current knowledge on A. pleuropneumoniae biofilm, factors associated with biofilm formation and dispersion, and the impact of biofilm on the pathogenesis A. pleuropneumoniae . We also provide an overview of current vaccination strategies against A. pleuropneumoniae and consider the possible role of biofilms vaccines for controlling the disease.